Quantitative analysis of shallow unreinforced and reinforced piled embankments with different heights subject to cyclic loads: Experimental study. Issue 138 (November 2020) - Aqoub, K.; Mohamed, M.; Sheehan, T.
Abstract: Reinforced piled embankment is an important technique which is widely used for construction on soft ground due to its benefits in reducing settlement, construction time and cost effectiveness. Most of the existing research has considered the response of deep embankments subjected to a uniform surcharge static load. Limited studies have examined the effect of cyclic loading or the influence of varying the height of the embankment. In this study, the effect of applying cyclic loading on a particular area of unreinforced and reinforced embankments of different heights was experimentally investigated and analysed. Twelve main experiments were undertaken to investigate the effects of monotonic and cyclic loading conditions, the number of reinforcement layers (n) and increasing the mean value and amplitude of the loading cycles on the behaviour of embankments of different heights. The experimental results showed that the transfer of loads to the piles was increased during the monotonic loading stage but at a lower rate with increasing the embankment height. Under cyclic loading conditions, arching of the soil was adversely affected during the initial stages of cyclic loading regardless of the embankment height. However, by increasing the number of cycles, arching of the soil started to regain some degree of improvement. Including layers of reinforcement increased the magnitude of the loads transferred on piles. However, the improvement was more obvious for a thinner embankment. Finally, the surface settlement increased with raising the embankment height but decreased when the number of reinforcement layers was increased, while the extent of heaving outside the loaded area was reduced with increasing both the embankment height and the number of reinforcement layers. Highlights: Irrespective of the embankment height, arching of the soil was adversely affected during the first 100 loading cycles. Increasing the number of cycles resulted in a degree of improvement on soil arching. Including layers of reinforcement made favourable impacts on the loads transferred to the central piles and the settlements. Surface settlement increased with increasing the embankment height but decreased when the number of reinforcement layers was increased.